Re-conceptualizing the gap as a potential space of becoming: Exploring aesthetic experiences with people living with dementia - Mittner, Lilli; Dalby, Karoline; Gjærum, Rikke Gürgens (Nordic Journal of Arts, Culture and Health, 2021)
Purpose: In this paper we describe how co-creative art practices can involve people living with dementia as active citizens. We build on the Nordic Relational Model of Disability (GAP model) that conceptualizes levels of functioning as a mismatch between individual abilities and requirements from the environment. Design: We explore how reciprocal aesthetic experiences from two residential care homes in Northern Norway can broaden a narrow biomedical understanding of dementia. Arts-based research and sensory ethnography are our methodological frames. We present three field descriptions that open an aesthetic universe through fine art, poetry and applied theatre. Findings: We find in our research that the gap between individual abilities and social requirements can become a space for creativity, in which everyone becomes connected and contributes to shared aesthetic experiences. We argue that broadening our understanding of the gap can result in new ways of relating to and being with each other. Originality: The paper advances aesthetic perspectives in dementia research.